Colorectal endometriosis and fertility. (February 2017) - Daraï, Emile; Cohen, Jonathan; Ballester, Marcos
Abstract: Objective: The goal of this review was to assess the impact of colorectal endometriosis on spontaneous fertility and the potential benefit of Medically Assisted Reproduction (MAR) ( in vitro fertilization and intrauterine insemination) and surgery on fertility outcomes. Study design: MEDLINE search for articles on fertility in women with DIE published between 1990 and December 2015 using the following terms: "deep endometriosis", "deep infiltrating endometriosis", "bowel endometriosis", "colorectal endometriosis", "fertility", "infertility", "IVF-ICSI", "Assisted Reproductive Techniques (ART)", and "MAR". Results: Spontaneous pregnancy rate (PR) in patients undergoing resection of DIE but leaving in situ colorectal endometriosis was 26.5% (95% CI = 14–39). PR after MAR was 27.4% (95% CI = 19–35) and the overall PR was 37.9% (95% CI = 29–37). After colorectal surgery, among the 855 patients with and without proved infertility, the spontaneous PR was 31.4% (95% CI = 28–34) without difference between the groups. PR after MAR was 19.8% (95% CI = 17–22). PR after MAR in patients with and without proved infertility was 21.4% (95% CI = 18–25) and 15.5% (95% CI = 11–20), respectively. The overall PR after colorectal surgery was 51.1% (95% CI = 48–54). Conclusion: Our review supports a potential benefit of surgery on fertility outcomes for women with colorectal endometriosis. Further studies are required to determine whether surgical management should be first-intention or restricted to failure of MAR.